KUKUM as an agent and role model in disaster preparedness and disaster management vis-à-vis the Malaysian Mechanism of Disaster Management - Azuddin, Bahari, Lt Kol (B) (International University, 2008)
Organized by International University, 4th - 7th December 2006 at International University, Cambodia.